Spectrum of gynecologic malignancies in Northeastern Nigeria - Katagum, Dauda A.; Ezenkwa, Uchenna S.; Achanya, Sunday E.; Lawan, Aliyu I.; Suleiman, Dauda E.; Kadaura, Mairo U.; Kabir, Abba; Adamu, Adamu I.; Modu, Abubakar Kolomi; Usman, Hadiza; George, Sophia H. L.; Schlumbrecht, Matthew; et al. (Frontiers in Oncology, 2025)
BackgroundThe burden of female genital tract cancers in low—and middle-income countries (LIMC) is not yet well investigated. Although available studies are few, they are mainly based on single institutions. Here, four-year multi-institutional data on gynecologic cancers in northeastern Nigeria were examined to determine their distribution by age and subtype.Patient and MethodsThis is a cross-sectional descriptive study using available data on histologically diagnosed gynecologic cancers archived in the pathology departments and/or cancer registries of six tertiary hospitals in northeastern Nigeria over four years. Alongside tumor type (according to site), patient age and presenting complaints were also documented. Descriptive statistics were used to present categorical variables as proportions, while quantitative variables of age were presented as medians.ResultsA total of 863 gynecologic cancers were included in this study. The median age was 50 years (3 – 95 years) with a peak at 40 – 49 years. The uterine cervix was the most common site of cancer (66.6%, 575/863), while uterine corpus (15.5%, 134/863) and ovarian cancers (14.8%; 128/863) were nearly equal in proportion. Squamous cell cancer was the commonest histotype overall, while ovarian cancers had a preponderance of epithelial tumors in 67.9% (87/128) over sex cord stromal (12.5%; 16/128) and germ cell (9.4%, 12/128) tumors. The most common symptom was abnormal vaginal bleeding (38%) followed by abdominal swelling (21.1%) and foul-smelling vaginal discharge (14.1%). Population-based data also showed high parity among women in the region, ranging from 4 births to 7 births per woman in a reproductive lifetime (total fertility rate, TFR).ConclusionThe spectrum of cancers of the female genital tract in this study mirrors the population demographics characterized by a high proportion of young women in their reproductive age. Efforts to reduce the burden of this disease are urgently warranted.